2022
DOI: 10.1093/jpids/piac084
|View full text |Cite
|
Sign up to set email alerts
|

Determining Time to Positivity of Blood Cultures in a Neonatal Unit

Abstract: Blood cultures are the gold standard for detecting bacteremia. We have studied the time to positivity of blood cultures in our neonatal unit to reduce antibiotic doses in patients with a negative blood culture. Empirical antibiotic treatment of neonatal sepsis could be withdrawn 24 hours after obtaining blood cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We determined this timeframe using unit-specific time-to-positivity data and studies published in similar patient populations. 25–27 We believe that limiting the duration of empiric antibiotics, in addition to ongoing education and stewardship practices, decreased the use of all monitored antibiotics and prevented an increase in the use of narrower spectrum agents with the implementation of our empiric algorithm. We acknowledge that automatic stop times may lead to unintentional interruptions in antibiotic therapy and require close monitoring by team members.…”
Section: Discussionmentioning
confidence: 99%
“…We determined this timeframe using unit-specific time-to-positivity data and studies published in similar patient populations. 25–27 We believe that limiting the duration of empiric antibiotics, in addition to ongoing education and stewardship practices, decreased the use of all monitored antibiotics and prevented an increase in the use of narrower spectrum agents with the implementation of our empiric algorithm. We acknowledge that automatic stop times may lead to unintentional interruptions in antibiotic therapy and require close monitoring by team members.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of antibiotic use in the NICU is in situations where the cultures are sterile and therein lies the relevance to every day NICU practice. (11) Recently, Arias-Felipe et al (25) have shown that in 98% of blood cultures from infants in the NICU, the time to positivity was < 24 hours. In addition, morbidity from a shortened course of empirical antibiotic therapy such as bronchopulmonary dysplasia, retinopathy of prematurity, necrotizing enterocolitis, and neurodevelopmental outcomes was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Arias-Felipe et al reported that 100% of gram-negative and 97.9% of gram-positive organisms grew within 24 hours in neonatal EOS and LOS. 34 Third, by only ordering a few doses of antibiotics for EOS and discussing the results of the blood cultures during the rounds of “time-out,” we compelled our providers to write a new order for antibiotic therapy and to justify further their decision to continue antibiotic treatment in the presence of a negative blood culture. The microbiology department’s immediate reporting of blood culture results in the EMR facilitated the implementation of this strategy.…”
Section: Discussionmentioning
confidence: 99%